2015
DOI: 10.1177/0192623315613452
|View full text |Cite
|
Sign up to set email alerts
|

PDGFR Inhibition Results in Pericyte Depletion and Hemorrhage into the Corpus Luteum of the Rat Ovary

Abstract: The growth plate, ovary, adrenal gland, and rodent incisor tooth are sentinel organs for antiangiogenic effects since they respond reliably, quantitatively, and sensitively to inhibition of the vascular endothelial growth factor receptor (VEGFR). Here we report that treatment of rats with platelet-derived growth factor receptor beta (PDGFRb) inhibitors that target pericytes results in severe ovarian hemorrhage with degeneration and eventual rupture of the corpus luteum. Evaluation of the growth plate, adrenal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…And concerning the crucial role of PDGFRβ–mediated interactions in recruitment of mural cells by newly formed vessels, genetic-induced disruption of PDGF-B or PDGFRβ leads to the development of microvascular leakage, lethal hemorrhage, and edema in late embryogenesis in mice 112 , 113 . Recently, using a rat model, Hall et al 114 showed that the use of specific PDGFRβ inhibitors resulted in pericyte depletion and hemorrhage into the corpus luteum of the ovary. In line with these findings, here we show that HF3 is able to cleave PDGFR (alpha and beta forms) and PDGF in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…And concerning the crucial role of PDGFRβ–mediated interactions in recruitment of mural cells by newly formed vessels, genetic-induced disruption of PDGF-B or PDGFRβ leads to the development of microvascular leakage, lethal hemorrhage, and edema in late embryogenesis in mice 112 , 113 . Recently, using a rat model, Hall et al 114 showed that the use of specific PDGFRβ inhibitors resulted in pericyte depletion and hemorrhage into the corpus luteum of the ovary. In line with these findings, here we show that HF3 is able to cleave PDGFR (alpha and beta forms) and PDGF in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Mice deficient in PDGFRβ completely lack brain pericytes and have increased BBB permeability that results in central nervous system microhemorrhages (Obermeier et al, 2013). Pharmacologic inhibition of PDGFRβ caused pericyte depletion and hemorrhage in rodents (Hall et al, 2016). Those findings indicate that blocking PDGFRα alone in the acute phase, without inhibiting the function of PDGFRβ, might provide an effective therapy for stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Luteinization is comprised of two major processes: 1) termination of proliferation with rapid hypertrophy and differentiation of steroidogenic follicular cells (granulosa cells and theca cells) into luteal cells, and 2) the rapid growth of blood vessels (angiogenesis) into the previous granulosa layer of the follicle 2 . Vascular endothelial growth factor (VEGF), angiopoietins, and platelet-derived growth factor (PDGF) play critical roles in luteal angiogenesis 2,10 .…”
Section: Key Factors In Luteinization After Ovulationmentioning
confidence: 99%
“…If direct toxicity in the adrenal cortex is observed, CL should be carefully evaluated considering their effect on steroidogenesis and vice versa. Since angiogenesis is a critical process for luteinization, CL should be carefully evaluated if any changes resulting from anti-angiogenesis are suspected in various organs/tissues (e.g., epiphyseal growth plate thickening, adrenocortical necrosis/hemorrhage, and incisor tooth dental dysplasia) 10,32 . When test article-related histopathological changes in CL are observed, it is important to determine whether the changes are caused by a direct effect or by other associated factors.…”
Section: Practical Approaches For the Evaluation Of Luteal Toxicity In Ratsmentioning
confidence: 99%
See 1 more Smart Citation